A comparison of methods used for quantifying internal training load in women soccer players - Alexiou, H.; Coutts, A. (International Journal of Sports Physiology and Performance, 2008)
Purpose: The purpose of this study was to compare the session-RPE method for quantifying internal training load (TL) with various HR-based TL quantification methods in a variety of training modes with women soccer players. Methods: Fifteen elite women soccer players took part in the study (age: 19.3 ± 2.0 y and VO2max: 50.8 ± 2.7 mL·kg-1·min-1). Session-RPE, heart rate, and duration were recorded for 735 individual training sessions and matches over a period of 16 wk. Correlation analysis was used to compare session-RPE TLs with three commonly used HR-based methods for assessing TL. Results: The mean correlation for session-RPE TL with Banister`s TRIMP, LTzone TL and Edwards`s TL were (r = 0.84, 0.83, and 0.85, all P < .01, respectively). Correlations for session-RPE TL and three HR-based methods separated by session type were all significant (all P < .05). The strongest correlations were reported for technical (r = 0.68 to 0.82), conditioning (r = 0.60 to 0.79), and speed sessions (r = 0.61 to 0.79). Conclusion: The session-RPE TL showed a significant correlation with all training types common to soccer. Higher correlations were found with less intermittent, aerobic-based training sessions and suggest that HR-based TLs relate better to session-RPE TLs in less intermittent training activities. These results support previous findings showing that the session-RPE TL compares favorably with HR-based methods for quantifying internal TL in a variety of soccer training activities.